2006
DOI: 10.1111/j.1423-0410.2006.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged storage of red blood cells affects aminophospholipid translocase activity

Abstract: This study shows that, although PS exposure remains low, prolonged storage does compromise the RBC membrane by affecting flippase activity. When the metabolic changes induced by storage are corrected, flippase activity can be restored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
61
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 23 publications
13
61
0
2
Order By: Relevance
“…Similar findings have been reported in studies of humans, in which only a small percentage of PS‐positive erythrocytes (3.5–4.5%) were detected after prolonged storage times of up to 7 weeks using similar techniques 11, 24, 25, 26. One possible explanation for why an increase in RBC PS expression was not detected is that the PS‐positive portions of the erythrocyte membrane could have been released from the cell and become microparticles in the unit.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings have been reported in studies of humans, in which only a small percentage of PS‐positive erythrocytes (3.5–4.5%) were detected after prolonged storage times of up to 7 weeks using similar techniques 11, 24, 25, 26. One possible explanation for why an increase in RBC PS expression was not detected is that the PS‐positive portions of the erythrocyte membrane could have been released from the cell and become microparticles in the unit.…”
Section: Discussionsupporting
confidence: 88%
“…For example, decreased deformability of stored RBCs may be ameliorated by correction of intracellular pH and restoration of adenosine triphosphate levels (36,60). Repletion of SNO-Hb levels during storage improved the vasodilatory function of RBCs in vivo (41).…”
Section: Mechanisms Linking Blood Transfusion With Excess Mortalitymentioning
confidence: 96%
“…16 This process is pH dependent and its rate increases with decreases in intracellular pH. 27 Verhoeven and colleagues 27 observed that storage of RBCs leads to a decrease in intracellular pH; intracellular pH of 7-week-stored human RBCs was as low as 6.36 while this was 6.83 in fresh human RBCs. This pH dependency might explain the differences between the hypoxia-induced NO formation rate in fresh and aged RBCs observed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…24 Earlier studies have demonstrated biochemical, structural, and functional changes of RBCs induced by extended cold storage. 19,22,[25][26][27][28] Despite lack of strong evidence, it is believed that depletion of NO bioavailability in relatively "aged" RBCs may provide an explanation for the functional loss of transfused aged RBCs. Several mechanisms have been described to explain such changes, such as depletion of S-nitrosohemoglobin or increasing amounts of cell-free Hb due to hemolysis during the storage process.…”
Section: Discussionmentioning
confidence: 98%